CARD9 in host immunity to fungal, bacterial, viral, and parasitic infections: An update - Hu, Ang; Hu, Zeming; Zou, Haohong; Zhang, Jiankang; Zhang, Dongliang; Wang, Hao; Zhong, Jianing; Chen, Bin (Frontiers in Microbiology, 2022)
Microbial infection, caused by fungi, bacteria, viruses, and parasites, is a major contributor to the death burden and health costs globally. As the human antimicrobial system, the innate and adaptive immune orchestrate a multifaceted signaling response to invading pathogens. In this process, caspase recruitment domain-containing protein 9 (CARD9) emerges as a critical intermediary adaptor molecule to participate in regulating a series of antimicrobial immune reactions. Previous publications have confirmed that CARD9 exerts a crucial role in fungal, bacterial, viral, and parasitic infections. In this review, we aim to provide an update on the recent clinical and basic studies where the mechanism and function of CARD9 have been further studied and understood. In addition, we summarize the latest treatment and prevention strategies based on CARD9 and discuss the current perspectives and prospective direction of CARD9.